Visitors' perception towards the service quality of Muzium Kesultanan Melayu Melaka / Kamal Rul Asraf Kamal Azmir , Siti Nur Syaffiqah Md Yasin and Nur Diyana Kamarudin - Kamal Azmir, Kamal Rul Asraf; Md Yasin, Siti Nur Syaffiqah; Kamarudin, Nur Diyana (Faculty of Hotel and Tourism Management, 2014)
Service quality have been a great impact towards organization's overall performance and revenues especially Tourism Industry where directly related with services. It is usually being achieved when visitor's satisfaction were fulfilled. Therefore. measuring visitor satisfaction becomes vital task in determining the future of the business.The purpose of this study is to identify, understanding and evaluate the level of visitor satisfaction toward service quality that had been provided in the museum in Melaka specifically Kesultanan Melayu Melaka museum using the SERVQUAL model developed by Parasuraman. Zeithaml and Berry. The study focused on identify the significant services dimension the influencing visitor perception and expectations. By using convenient sampling. the result indicates that some of the service dimensions should be improved in order to increase visitor satisfaction such as tangibles and reliability of the museum. Other dimensions such as responsiveness. empathy and assurance should be maintain or to be improved time to time. The data was computed using SPSS program and analyzed. The further explanations are discussed under this research.